Little liar a novel - Albom, Mitch (New York, NY Harper, an imprint of HarperCollinsPublishers, 2023)
Eleven-year-old Nico Crispi never told a lie. When the Nazi's invade his home in Salonika, Greece, the trustworthy boy is discovered by a German officer, who offers him a chance to save his family. All Nico has to do is convince his fellow Jewish residents to board trains heading towards "the east" where they are promised jobs and safety. Unaware that this is all a cruel ruse, the innocent boy goes to the station platform every day and reassures the passengers that the journey is safe. But when the final train is at the station, Nico sees his family being loaded into a large boxcar crowded with other neighbors. Only after it is too late does Nico discover that he helped send the people he loved--and all the others--to their doom at Auschwitz. Nico never tells the truth again.
112607
Keywords: World War -- Jews -- Fiction. -- 1939-1945; Holocaust, Jewish -- Fiction. -- (1939-1945); Nazi concentration camps -- Fiction; Truthfulness and falsehood -- Fiction; Manipulative behavior -- Fiction; Holocaust survivors -- Fiction; Holocauste -- Romans, nouvelles, etc. -- 1939-1945; Manipulation (Psychologie) -- Romans, nouvelles, etc; World War -- Jews -- Fiction. -- 1939-1945; Holocaust -- Fiction. -- 1933-1945; Crete (Greece) -- History -- Occupation, 1941-1945 -- Fiction; Thessalonike (Greece) -- Fiction; Historical fiction; Psychological fiction; Novels; Romans